Результати експериментальних досліджень роботи повітряного ґрунтового теплообмінника - Долгіх, Д. О.; Ковязін, О. С.; Ренсевич, Є. О.; Dolgikh, Denis; Kovyazin, Alexey; Rencevich, Eugenie (КНТУ, 2013)
Проведені експериментальні дослідження роботи повітряного ґрунтового теплообмінника, визначені оптимальні параметри при роботі ґрунтового повітряного теплообмінника. To determine experimentally – optimal operating parameters, the effective thermal capacity of the airground heat exchanger was the purpose of work. This paper deals with the description of the experimental apparatus – air-ground heat exchanger, of the varied factors – the volumetric air feeding Q, m3/h., the time of the work of the geothermal ventilation t, sec., the outside air temperature T1°C, and parameter of optimization – effective heat power P, W. Based on the data obtained from the experimental apparatus, was received the equation of regression, which describes investigated process to the parameter of the optimization. According to the analysis of the investigated factors obtained response surface. The resulting optimum of equation describes that the maximum effective heat power equal to 750W, in the following conditions: the volumetric air feeding (Q, m3/h) is equal to 403.8 m3/h; the time of the work of the geothermal ventilation (t, sec.) is equal to 0 sec.; the outside air temperature (T1°C) is equal to 340C. With increasing of the temperature, at the inlet to air-ground heat exchanger be on the increase the output of the thermal energy. With the decline of the volumetric air feeding increases the output of the thermal energy, but to a certain limit (200m3/h). Time of the operation of the geothermal ventilation affects the energy extraction. As longer works the air-ground heat exchanger thereby intensive occurs temperature increase at the outlet of air-ground heat exchanger.
The Results of the Experimental Studies of the Air Ground Heat Exchanger
Keywords: геотермальна вентиляція; ґрунтовий теплообмінник; математична модель; теплова потужність; geothermal ventilation; ground heat exchanger; a mathematical model; the thermal power